GMAT 2003 with CD-ROM - Kaplan, Inc. (New York Kaplan Educational Centers :Simon & Schuster, 2002)
Presents strategies and tips, and offers sample questions and answers for the math, verbal, and analytical sections.
At head of title: Kaplan GMAT.
"July 2002"--Title page verso.
Keywords: Graduate Management Admission Test -- Study guides; Universities and colleges -- United States -- Graduate work -- Examinations -- Study guides